Implementation of Kid Animation on Youtube as Learning Media in Teaching Vocabulary to Young Learners - Oktrianur, Hafirsyani Rizka (Universitas Negeri Surabaya, 2022)
This study mainly discussedteachers’ experiences related to the implementation and problems while using kid animations on YouTube as one of the learning media in the context of teaching vocabulary to young learners. Indeed, kid animations are suitableto be implemented by teachers in this advanced era because ofthe technology’s development. On the one hand, teaching vocabulary to young learners belongs to a significant matter since vocabulary itself is the main foundation for a person who wants to learn a language, especially for young learnerswho have an audio-visual learning style.So, this study was designed as qualitative researchby using 2 instruments, which were: observation, and open-ended interviews with 2 English 5thgrade teachers in one of Islamic school in Sumenep, East Java, Indonesia.The result of this study revealedthat the 3 stepsof the implementation of this learning media starting from: Pre-implementing, while-implementing, and post-implementing couldbe utilizedso wellin the class. Furthermore, the study showedthat the teachers have solutive ways when they face several obstacles in using thislearningmedia. Therefore, the researcher claimed that this study will help and inform the readers when they want to apply kid animations on YouTube as attractive learning media in teaching vocabulary to young learners.